The major epidemiologic, microbiologic, immunologic, and clinical aspects of Lyme disease that form the basis for a newly developed vaccine that may become available soon for human use - Pavia, Charles S.; Saggio, Gregory; Plummer, Maria M. (Frontiers in Immunology, 2024)
Working together, two pharmaceutical companies have developed a Lyme disease vaccine consisting of recombinant-derived outer surface protein A (OspA) of the etiologic agent Borrelia burgdorferi. Multiple clinical trials have shown the vaccine to have good safety and efficacy results, and it is hoped that it would become available for human use at least by the year 2025 after receiving approval from the U.S. Food and Drug Administration. There are still challenges left to ensure that the vaccine has, at most, minimal side effects. Also, because the previously developed Lyme disease vaccine was discontinued in 2002 after four years of distribution, due mostly for frivolous reasons having little or no scientific basis, that even led to legal entanglements involving the vaccine manufacturer and some of the medical personnel overseeing the clinical trials, there will be concerns that this newly developed one could be subject again to some of the same unnecessary scrutiny rendering its implementation suboptimal. Initially this review will focus on the key epidemiological, microbiologic, immunologic and clinical aspects of Lyme disease that provide the foundation for developing this type of vaccine that could have a serious impact on the prevalence of this and even certain other tick-transmitted infection.